Children with Epistaxis and Risk Factors for Bleeding Disorders: Importance of Preoperative Diagnostic - Mansoor Alam, Humaira Khan, Shabir Ahmed Orakzai, Muhammad Hafeez, Siyab Ahmad, Bilal Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of previously undetected bleeding problems in kids with severe epistaxis who required intraoperative nasal cautery after failing medicinal treatment. Study design: Retrospective study Setting: Khyber Teaching Hospital Peshawar . Subjects and methods: Children (under the age of 19) with epistaxis who have been referred to an otolaryngologist must also have no known bleeding disorders, have had surgical nasal cautery, and have failed medicinal treatment. Information gathered includes epistaxis duration/severity, past bleeding patterns, and bleeding in the family. All patients had a screening CBC, PT, and PTT. Results: 47 (19%) of the 248 participants who were referred for epistaxis matched the inclusion criteria (mean age 9.2 0.5 years;61.7 percent male). 31.9 percent (15/47) of the patients had abnormal coagulation findings, however only 2 patients continued to have them after repeat testing. 15 patients were sent to haematology, where 5 had bleeding disorders (3 had type 1 von Willebrand's disease, 1 had a condition of platelet aggregation, and 1 had minor factor VII insufficiency). 10.6% (5/47) of the group as a whole had a bleeding disorder. Previous trips to the emergency department for epistaxis were one of the clinically significant predictors of developing a bleeding disorder (p = 0.04). Younger patients who presented with epistaxis showed a tendency (p = 0.07). Conclusion: Children who have repeated epistaxis while receiving medical treatment are more likely to develop a bleeding condition. 10.6% (5/47) of the patients in this highly selected cohort were found to have a bleeding condition. Only 20% (1/5) of individuals with a bleeding issue were identified by screening coagulation testing (PT, PTT). In most individuals, the diagnosis was not made until after a thorough haematology examination. Keywords: epistaxis, bleeding disorders, children, diagnostic